Pengaruh Kualitas Produk, Citra Merek danGaya Hidup terhadap Keputusan Pembelian Produk Merek Consina di Surabaya (Studi Kasus Pada Consina Store Dharmahusada Surabaya) - Rahmawati, Silviya; Pratiwi, Ni Made Ida; Tjahjono, Endro (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACT Lately, more and more teenagers are doing outdoor activities or activities that are identical with adventure in the wild which has become a new lifestyle behind the glitter of technology in modern times. To be able to attract consumer buying interest, companies must strive to improve and maintain product quality with an appropriate selling price offset, and be able to answer the needs and desires of consumers. This study aims to determine the effect of product quality, brand image, and lifestyle on the purchasing decisions of Consina brand products at the Dharmahusada Store in Surabaya. The population in this study are consumers who have purchased Consina brand products at the Dharahusada Store in Surabaya. This study uses a purposive sampling technique to determine respondents as many as 100 people. The data collection method uses a questionnaire. The analysis used in this study is multiple linear regression analysis, F test, t test, coefficient of determination. The results of this study indicate that the quality of products, brand image, and lifestyle silmutan influence on purchasing decisions. Product quality, brand image and lifestyle partially influence purchasing decisions. Keywords: Product Quality, Brand Image and Lifestyle